Cutting edge: IFN-γ regulates the induction and expansion of IL-17-producing CD4 T cells during mycobacterial infection - Cruz, Andrea (2006)
T cell responses are important to the control of infection but are deleterious if not regulated. IFN-γ-deficient mice infected with mycobacteria exhibit enhanced accumulation of activated effector T cells and neutrophils within granulomatous lesions. These cells do not control bacterial growth and compromise the integrity of the infected tissue. We show that IFN-γ-deficient mice have increased numbers of IL-17-producing T cells following infection with Mycobacterium bovis bacille Calmette Gue´rin. Furthermore, exogenous IFN-γ increases IL-12 and decreases IL-23 production by bacille Calmette Gue´rin-infected bone marrow-derived dendritic cells and reduces the frequency of IL-17-producing T cells induced by these bone marrow-derived dendritic cells. These data support the hypothesis that, during mycobacterial infection, both IFN-γ- and IL-17-producing T cells are induced, but that IFN-γ serves to limit the IL-17-producing T cell population. This counterregulation pathway may be an important factor in limiting mycobacterially associated immune- mediated pathology.